Republic of Palau : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Palau. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2019)
This Article IV Consultation discussions with the Republic of Palau focused on ensuring long-term fiscal sustainability, making potential growth more resilient and sustainable, and preserving financial stability and facilitating credit extension. The consultation discussions also highlight that the main economic policy priorities for Palau are to develop a medium-term fiscal framework and strategy to help manage fiscal risks and the expiration of the Compact grants, to raise public investment, to protect social spending, to make growth more resilient and sustainable through other reforms, and to preserve financial stability and integrity. The current fiscal policy approach is based on the legal requirement to maintain a balanced or surplus cash flow for various parts of the budget. While this fiscal policy strategy has resulted in overall budget surpluses and a decline in net debt, the move to a medium-term fiscal framework and strategy would help Palau to address future challenges.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet